The Interplay of Regional and Ethnic Inequalities in Malaysian Poverty Dynamics - Rongen, Gerton (World Bank, Washington, DC, 2022)
This study employs a synthetic panel approach based on nationally representative micro-level data to track poverty and income mobility in Malaysia in 2004–16. On aggregate, there were large reductions in chronic poverty and increases in persistent economic security, but those who remained poor in 2016 were increasingly likely to be poor in a structural sense. Further, the poverty and income dynamics differ notably across geographic dimensions. Such disparities are most striking when comparing affluent urban Peninsular Malaysia with poorer rural East Malaysia. Although there are important differences in welfare levels between the main ethnic groups in Malaysia, the mobility trends generally point in the same direction. While the findings show that there is still scope for poverty reduction through the reduction of interethnic inequalities, the study underscores the importance of taking regional inequalities into account to ensure a fairer distribution of socioeconomic opportunities for poor and vulnerable Malaysians. Hence, addressing chronic poverty is likely to require additional attention to less developed geographic areas, as a complement to the current policies that are largely ethnicity-based.